Impacto del Covid-19 en las actividades económicas - financieras de las Cooperativas de Ahorro y Crédito del segmento cinco - Nevárez Macías, Andy Jair (2024)
The main objective of this research was to analyze how COVID-19 affected the economic and financial activities of Ecuadorian savings and credit cooperatives in segment five. Historical financial statement data from 2019 to 2023 were examined, and a sample of 52 entities from segment five was selected, providing continuous accounting information to the Superintendence of Popular and Solidarity Economy for evaluation. Various methodologies and techniques were employed, such as cross-sectional, causal, bibliographic, exploratory, and quantitative research, along with analytical and descriptive methods. Tools like literature review, financial analysis, forecasting, and the PERLAS monitoring system were also part of the study. To obtain the results, three methodological phases were structured. In the first phase, horizontal and vertical analysis of the balance sheet and income statement were conducted to compare historical data. In the second phase, financial indicators established by the PERLAS methodology were calculated and analyzed to identify variations over the last four years. In the final phase, the PERLAS components' indicators were projected to determine the future behavior that cooperatives will experience in the next five periods. As a result, a negative impact on the economic and financial activities of segment five COACs during the years 2020, 2021, and 2022 was identified.